Paper 15: Micro-Fragmented Adipose Tissue versus Platelet-Rich Plasma for the Treatment of Knee Osteoarthritis: A Prospective Randomized Controlled Trial at 2-year follow-up. Issue 7 (30th July 2022) - Di Martino, Alessandro; Andriolo, Luca; Boffa, Angelo; Poggi, Alberto; Kon, Elizaveta; Filardo, Giuseppe; Zaffagnini, Stefano
Objectives: Pre-clinical and clinical studies supported the use of intra-articular micro-fragmented adipose tissue (MF-AT) injections to address knee osteoarthritis (OA), suggesting their safety and clinical benefits. Nevertheless, no high-level studies investigated the potential of MF-AT over other biological products like platelet-rich plasma (PRP). The aim of this randomized controlled trial (RCT) was to compare a single injection of MF-AT to PRP in terms of clinical outcome and disease-modifying properties in patients with symptomatic knee OA. Methods: A total of 118 patients with symptomatic knee OA were randomly assigned to: single intra-articular MF-AT vs single intra-articular PRP injection. All patients were evaluated before the injection and at 1, 3, 6, 12, and 24 months with the International Knee Documentation Committee (IKDC) subjective score, the Knee injury and Osteoarthritis Outcome Score (KOOS) pain subscales, the EuroQol-Visual Analogue Scale (EQ-VAS) and EuroQol-5D (EQ-5D), and the Visual Analogue Scale (VAS). The treated knees were evaluated at baseline and at 6, 12, and 24 months of follow-up with radiographs and high-resolution (1.5 T) magnetic resonance imaging (MRI) with the Whole-Organ Magnetic Resonance Imaging Score (WORMS). Results: Both MF-AT and PRP provided a statistically and clinically significant improvement up to the last follow-up of 24 months. No differences were found between MF-AT and PRP groups in terms of adverse events (18.9% vs 10.9%), failures (15.1% vs 25.5%), and all clinical outcomes at all follow-ups. Radiographs and MRI findings did not show significant changes after the injection, neither as improvement, nor as disease progression, with no intergroup difference. Patients with moderate/severe OA treated with MF-AT showed a significantly higher IKDC improvement at 6 months compared to PRP (15.7±19.0 vs 8.6±14.2, p=0.041). Similarly, more patients with moderate/severe OA treated with MF-AT reached the minimal clinically important difference (MCID) for the IKDC subjective score at 6 months compared to the PRP group (75.0% vs 34.6%, p=0.005). Conclusions: A single intra-articular injection of both MF-AT and PRP provided a significant clinical improvement up to 24 months in patients with symptomatic knee OA. Both treatments showed a comparable low number of failures and adverse events, without signs of disease progression. Overall, no differences could be documented in both clinical and imaging results between the two biological approaches. Compared with PRP, MF-AT provided a higher clinical improvement at 6 months in moderate-severe OA.